Latent Fingermark Imaging by Single-Metal Deposition of Gold Nanoparticles and Surface Enhanced Raman Spectroscopy - Kolhatkar, Gitanjali; Parisien, Cédric; Ruediger, Andreas; Muehlethaler, Cyril (Frontiers in Chemistry, 2019)
In forensic science, there is a high demand for a technique that allows the revelation of fingermarks invisible to the naked eye as well as the chemical information they contain. Here, we present a feasibility study consisting in using both the luminescence enhanced by surface plasmon of gold nanoparticles, and the surface enhanced Raman spectroscopy signal of fingermark chemical components to image latent fingermarks. A latent fingermark deposited on a transparent glass substrate is visually revealed using single-metal deposition employing gold nanoparticles. The resulting enhanced luminescence is monitored over a revealed area of the latent fingermark, displaying light regions of 200-400 µm, corresponding to the fingermark ridges. The Raman signal of the fingermark’s chemical components is enhanced into a measurable signal. Imaging those Raman peaks reveals the ridges pattern, attesting to the potential of our method.